Does Leadership Style and Work Environment Influence Employee Performance? The Mediating Role of Job Satisfaction - Ni’matul A’inah; Ratna Kusumawati (Universal Business and Management Review, 2025)
Human resource strategic planning is needed to achieve better in a tight competition, included job satisfaction and employee performance. This study aims to analyze the influence of leadership style, work environment mediated by job satisfaction, on employee performance. This study uses a quantitative approach and uses primary data using a questionnaire. The population used in this study was 50 employees of Griya Anyam Jepara. Data analysis used quantitative methods with the help of SPSS 25. The results indicate that leadership style has a positive and significant effect on employee performance, and work environment has a positive and insignificant effect on employee performance. Through the path analysis, leadership style has a positive and significant effect on employee performance mediated by job satisfaction. Further findings indicate work environment has a positive and insignificant effect on employee performance mediated by job satisfaction. The study concludes that a good leadership style and work environment will influence employee satisfaction and have an impact on employee performance.